1948
DOI: 10.1149/1.2773794
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemistry of Indium

Abstract: Recently revived interest in indium chemistry has demonstrated the importance of electrochemical studies and data. Available electrochemical information is useful in evaluating the ease of reduction of indium compounds, the ease of oxidation of the metal, the relative ionic characteristics of the compounds in the pure conditions and in solution, and the quantitative estimation of the element. The quantity production of indium metal in a high state of purity is based primarily upon knowledge of its electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1953
1953
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Experiments have indicated that the disproportionation reaction is quantitative. Since both Cd and Zn are more negative than In in the electromotive series (3,16), the presence of CdCI~ and ZnCI~ in the fused salt bath does not interfere with the reaction in any way; the resulting In metal is spectroscopically free of Cd and of Zn.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments have indicated that the disproportionation reaction is quantitative. Since both Cd and Zn are more negative than In in the electromotive series (3,16), the presence of CdCI~ and ZnCI~ in the fused salt bath does not interfere with the reaction in any way; the resulting In metal is spectroscopically free of Cd and of Zn.…”
Section: Methodsmentioning
confidence: 99%
“…This subject has been treated by others (2). The tendency of compounds of indium to be relatively nonionic or covalent in their bonding is felt to be one of the more important properties of this element which influences its metallurgy.…”
Section: Electrochemistry Of Indiummentioning
confidence: 99%
“…Indium possesses a high hydrogen overvoltage (1), near that of Hg and its standard potential is close to that of Cd. These two properties indicated that it might be useful as an energy producing anode and might show less tendency toward parasitic reactions which promote deterioration of commercial cells during storage.…”
mentioning
confidence: 99%